Metabolic and respiratory consequences of wastewater exposure in fish - Du, Sherry (My University, 2017)
Wastewater effluent is a major source of aquatic pollution, discharging a continuous and complex mix of contaminants into the environment. The physiological impacts of exposure to individual contaminants are well characterized in fish, but less is known about the consequences of complex mixtures that typify wastewater effluent in the environment. This thesis explores the metabolic and respiratory effects of in situ wastewater exposure on bluegill sunfish (Lepomis macrochirus). By assessing multiple levels of biological organization, I provide evidence that wastewater exposure invoked a metabolic cost in bluegill, which was associated with physiological adjustments to enhance oxygen uptake, delivery, and utilization. These findings broaden our understanding of how fish tolerate life in effluent-dominated waters and support the emergence of metabolic and respiratory physiology as biomarkers in ecotoxicology.
Keywords: physiology; aquatic biology; ecotoxicology; Cootes Paradise Marsh; wastewater; metabolism; respiration; fish